Design and Synthesis of N-Phenyl-2-(Phenyl-Amino) Acetamide Derivatives as FVIIA Inhibitors for Effective Anticoagulant Activity - Momin, Yasmin Hamid; Desai, Shailaja Prakash; Chavan, Pranali Ananda (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim Factor Vila is a glycosylated disulfide-linked heterodimer that belongs to the serine protease family involved in the coagulation process. Inhibition of factor Vila is one of the crucial targets for novel anticoagulant agents. Coagulation factor Vila inhibition has recently attracted attention as an intriguing antithrombotic therapeutic strategy. With the aid of X-ray crystallography and structure-based design, we were able to discover a novel series of N-phenyl-2-(phenyl-amino) acetamide derivatives that exhibited a remarkable affinity for factor Vila. Materials and Methods The synthesis of 22 compounds was based on the Schotten-Baumann reaction. The synthesized compounds were confirmed by physicochemical, spectroscopic and elemental analysis. In vitro, anticoagulant activity was evaluated using prothrombin determination method. Results Compounds 4, 7, 15, 16 and 19 demonstrated good inhibitory anticoagulant activities in vitro and showed good docking score in silico. N-phenyl-2-(phenyl-amino) acetamide provides a good template for the synthesis of novel and potent anticoagulant derivatives. Conclusion N-phenyl-2-(phenyl-amino) acetamide derivatives can be serving as potential drug compounds for coagulation disorders. The objective of this study was to employ in silico molecular docking and in vitro anticoagulant activity to design and synthesize structure-based new factor Vila inhibitors with enhanced potency.
Keywords: N-phenyl-2-(phenyl amino) acetamide; Factor Viia; Pyrex; X-ray crystallography; Prothrombin time